Asuhan Keperawatan Pada Tn.A Dengan Gangguan Sistem Pernafasan Luka Trakheostomi - Miftahul Jannah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Tracheostomy is the act of creating a stoma or hole so that air can enter the lungs by bypassing the upper airway. Tracheostomy can be performed as an operative procedure which aims to create a new airway in the trachea by making an incision or incision in the 2nd, 3rd, 4th tracheal rings. Case study design: The type of research used is a descriptive observational research design with a case study approach in patients diagnosed with respiratory system disorders, Tracheostomy wounds, namely a research design that includes an intensive study of one research unit: for example one patient, family group, group, or institution. Although the number of subjects tends to be small, the number of variables studied is very broad. The focus of this case study is "diagnosing respiratory system disorders with tracheostomy wounds. Types and methods of data collection and data collection techniques used in writing the results of this case study are primary and secondary data. The results show that the tracheal stoma post laryngectomy is a permanent tracheostomy. Tracheal cartilage is directed to the surface of the skin, attached to the neck. The rigidity of the cartilage keeps the stoma open so that a tracheostomy tube (canule) is not needed. Tracheal stoma without laryngectomy: is a temporary tracheostomy. The trachea and upper airway are intact but there is obstruction. A tracheostomy tube (canule) made of metal or non-metal is used (especially in patients who are receiving radiation and during.